Terra nova, provinciae novae? Roman intervention and Roman power in the western Mediterranean, ca.295-167 BC. - Potter, DL (2019)
Between 295 and 167 BC, Rome’s position in the western Mediterranean changed hugely. This thesis asks how. It does this through the consideration of three specific regions: Sicily, the Iberian Peninsula, and Gallic northern Italy, each of which occupies a section, containing two chapters. The two chapters on each region aim to address two separate but related questions: how did Rome become directly involved in the region; and how did it subsequently manifest power there?